2020
DOI: 10.1007/s10067-020-05502-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated microRNA expression in rheumatoid arthritis families—a comparison between rheumatoid arthritis patients, their first-degree relatives, and healthy controls

Abstract: Objective Recent studies have demonstrated an altered expression of certain microRNAs in patients with rheumatoid arthritis (RA) as well as their first-degree relatives (FDRs) compared to healthy controls (HCs), suggesting a role of microRNA in the progression of the disease. To corroborate this, a set of well-characterized RA families originating from northern Sweden were analyzed for differential expression of a selected set of microRNAs. Method MicroRNA was isolated from frozen peripheral blood cells obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Previously reported miRNAs in RA-FLS were predicted from mRNAs based on various bioinformational platform, and these mRNAs were not analyzed at a Weighted Correlation Network Analysis (WGCNA). There are numerous miRNAs can be further investigated in RA-FLS's biological characteristics (6)(7)(8). To further identify the miRNAs in RA-FLS, we performed miRNA and mRNA-sequencing on FLS from 3 RA patients, FLS from 3 trauma patients as the control.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported miRNAs in RA-FLS were predicted from mRNAs based on various bioinformational platform, and these mRNAs were not analyzed at a Weighted Correlation Network Analysis (WGCNA). There are numerous miRNAs can be further investigated in RA-FLS's biological characteristics (6)(7)(8). To further identify the miRNAs in RA-FLS, we performed miRNA and mRNA-sequencing on FLS from 3 RA patients, FLS from 3 trauma patients as the control.…”
Section: Introductionmentioning
confidence: 99%
“…Among the sncRNAs, micro-RNAs (miRNAs) can regulate gene expression mainly through combining with the 3́untranslated regions (3́UTRs) of target messenger RNA (mRNA). Altered expression levels of a number of miRNAs, including miR-22-3p, miR-26b-5p, miR-142-3p, and miR-155 have been also confirmed in RA patients (19). Moreover, serum expression of miR-224, miR-760, miR-483-5p, miR-378 and miR-375 was found to be significantly upregulated and it seems to correlate with the DAS28 score in RA patients (20), while miR-NA-22 appears to be associated with disease activity in well-established RA (21).…”
Section: Genetic Aspectsmentioning
confidence: 87%
“…MiR-142-3p is located on human chromosome 17 and can play an important role as an anti-inflammatory or proinflammatory gene in inflammation-related diseases ( Hu and Wang, 2016 ; Zhang et al, 2020a ). For example, miR-142-3p is involved in the regulation of OA ( Gao et al, 2019 ), rheumatoid arthritis (RA) ( Renman et al, 2021 ) and GA ( Bohatá et al, 2021 ). Wang et al (2016) found that the expression of miR-142-3p was reduced in mice with OA and had a targeted regulatory role with high mobility group box 1 (HMGB1).…”
Section: The Functional Role Of Micrornas In Gouty Arthritismentioning
confidence: 99%
“…Upregulation of miR-142-3p expression inhibited chondrocyte apoptosis and inflammation. MiR-142-3p was also found to be aberrantly expressed in RA patients compared to healthy controls ( Renman et al, 2021 ). Most recently, Bohatá et al (2021) detected the expression of miR-142-3p in the plasma of normal uric acid controls, hyperuricemia and gout patients, and the results showed that the expression of miR-142-3p was upregulated in hyperuricemia and gout patients.…”
Section: The Functional Role Of Micrornas In Gouty Arthritismentioning
confidence: 99%